(untitled) (Research, Society and Development, 2020)
It is common for young people adopt negative health behaviors because of changes in lifestyle and leisure habits. Physical Education students appear to adopt health risk behaviors even acquiring knowledge about healthy habits during graduation. Thus, the objective of the study was to relate leisure habits with the lifestyle behaviors of university students. The sample consisted of students from bachelor’s and undergraduate degrees in Physical Education at the Londrina’s State University. The instruments for data collection were: Sociodemographic Questionnaire, Leisure Habits Scale and Fantastic Lifestyle Questionnaire. The analysis of sociodemographic characteristics characterized the sample. To verify the relationship between leisure habits and the students’ lifestyle, Spearman’s correlation coefficient was used. In all analyzes, the 95% significance level was adopted (p <0.05). The correlation indexes between leisure habits and lifestyle showed that the choice of leisure habits significantly interferes with the dimensions of lifestyle and it was possible to observe that there are distinctions between the behaviors of bachelor’s students compared to undergraduate students.